PENGARUH INTRODUKSI ISOLAT RIZOBAKTERIA INDIGENUS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENTANG (Solanum tuberosum L.) DAN DINAMIKA POPULASI GULMA DI ALAHAN PANJANG, SUMATERA BARAT - FRISKIA HANATUL QOLBY; IRAWATI CHANIAGO; INDRA DWIPA; ZURAI RESTI (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Potato (Solanum tuberosum L.) is of important major crops for its carbohydrate and plays important roles to support food sovereignty along with rice, wheat, corn, and sorghum. Potato growth and yield at West Sumatra has not reached its maximum potential due to some factors including cultivation. One major important constraint in potato growing in West Sumatra is the fact that farmers use the 8th to 12th generation of potato seedlings which have a very low agronomic potential. Yet, weeds have caused another problem in the field and reduce potato yield. An experiment has been conducted at the Laboratory of Microbiology, Faculty of Agriculture, Universitas Andalas and Nagari Alahan Panjang, Subdistrict Lembah Gumanti, Solok Regency from November 2018 to March 2019. The experiment was aimed at determining the best indigenous rhizobactria isolates to increase the growth and yield of potato plants as well as weed population dynamics associated with potato plants. Six isolates of indigenous rhizobacteria and a control treatment group were tested in a completely randomised design with three replicates. The isolates were L1 S3.1, L1 S3.2, L1 S4.4, L2 S1.2, L2 S2.3, L2 S3. 2. Data were analyzed with analysis of variance and mean separation with Duncan's New Multiple Range Test (DNMRT) at 5%. Results showed that isolate L1 S4.4 was best in increasing the number of branches, number of tubers, and weight of potato yield. The isolates tested affected weed populations dynamics, prior to treatments there were 8 species of weeds found at the field i.e Bidens pilosa L., Leptochloa chinensis, Eleusine indica L., Agerathum conyzoides, Richardia sp, Galinsoga parviflora, and Sonchus arvensis. During potato growing at the field, weed species of Eleusine indica L. and Gynura divaricata dissappeared from the soil. In contrast, Amaranthus spinosus emerged demonstrating that weed population dynamic has occurred.